Oral lichen planus and the Thr102Cys polymorphism of HTR2A: a pilot case-control study. (July 2022) - Michelon, Isabella Ferreira; do Amaral, Cainá Corrêa; Garcia, Tiago Fernandez; Corrêa, Geovanna Peter; Klug, Adriana Beiersdorff; da Silva, Karine Duarte; Vasconcelos, Ana Carolina Uchoa; Tarquinio, Sandra Beatriz Chaves; Nedel, Fernanda
Abstract: Background: Oral cancer is one of the most common types of cancer in the world, leading to over 177 000 deaths worldwide annually. The literature suggests that oral cancer might be preceded by potentially malignant oral lesions, such as oral lichen planus, a multifactorial chronic inflammatory condition with an autoimmune component. Smoking and alcohol consumption are two of the many triggers of oral lichen planus and oral cancer. Both habits have likewise been associated with the Thr102Cys polymorphisms in the HTR2A gene, which codes the 5-hydroxytryptamine receptor 2A (5-HT-2A). The aim of this study was to investigate the Thr102Cys polymorphism rs6313 (NG_013011.1:g.6230C>T on GenBank) in the HTR2A gene in patients with oral lichen planus, and to explore its association with smoking and alcohol consumption. Methods: This case-control study took place in 2009–16 in the Centre of Diagnosis of Oral Diseases of the Federal University of Pelotas, Brazil, a national reference centre in histopathological diagnosis. Women aged 18 years or older with a histopathological diagnosis of oral lichen planus and healthy controls aged 18 years or older were included. Each group included patients with and without smoking or alcohol consumption habits. Men and patients with other conditions were excluded. Cell samples from oral lesions were collected with cytological brushes (QIAamp DNA FFPE Tissue Kit, Qiagen, Hilden, Germany) for DNA extraction, and the Thr102Cys polymorphism was genotyped using 40x Human Custom TaqMan Genotyping Assay primers and probes (Life Technologies, Foster City, CA, USA). The study was approved by the Research Ethics Committee of the Federal University of Pelotas (reference 058/2008) and written consent was obtained from all participants. Statistical analyses were done with the Statistical Package for Social Sciences version 16.0. Categorical variables were analysed with the Chi-square test. Logistic regression analysis was presented by odds ratios (OR) and 95% CIs to evaluate the risk of Thr102Cys single nucleotide polymorphism in patients with oral lichen planus. Findings: 108 individuals were included (46 cases and 62 controls). Median age was 58 years (IQR 51–68). Significant differences were noted between patients in the control and oral lichen planus groups: smoking habits (p<0·0001), alcohol consumption (p=0·035), and presence of the Thr allele (p=0·021) were all higher in the control group. The adjusted logistic regression analysis showed that smokers had a reduced risk (OR 0·18 [95% CI 0·05–0·60]; p=0·005) of developing oral lichen planus compared with non-smokers. Moreover, individuals carrying the Thr allele in the Thr102Cys polymorphism also had a reduced risk (0·19 [0·05–0·67]; p=0·010) of developing oral lichen planus. Interpretation: Our results show that oral lichen planus is associated with the presence or absence of the Thr102Cys polymorphism and smoking habits. Although tobacco is a known carcinogen, the presence of the Thr allele in smokers might offer a protective effect to oral lichen planus development. Serotonin induces signalling cascades and platelet aggregation via 5-HT-2A, so even slight mutations might modify the receptor's function. Also, studies suggest that tobacco could alter and suppress immunological mechanisms. Considering the sample median age and that aging also affects immunity function, it is possible that mutations on 5-HT-2A receptors along with the tobacco immunosuppression might be beneficial in preventing immune-mediated disorders such as oral lichen planus. Nevertheless, it is noteworthy that the adverse effects of smoking far outweigh any benefits shown by this association. Funding: None.